ANATOMY AND CRANIAL MORPHOMETRY OF PAROARIA DOMINICANA (LINNEAUS, 1758): anatomia e morfometria craniana do paroaria dominicana (LINNEAUS, 1758). - Teixeira, Rafaela Dantas; Santos, Raisla de Lima; Oliveira, Caio Ian Delfino; Alves, Thaís de Oliveira; Carreiro, Artur da Nóbrega (Revista de Ciências da Saúde Nova Esperança, 2026)
Paroaria dominicana (Linnaeus, 1758) is a species whose habitat predominates within national territory, occurring across the Northeast, Southeast, North, and part of the Central-West regions of Brazil. This species, commonly known as the “galo-de-campina” (red-cowled cardinal), belongs to the kingdom Animalia, class Aves, order Passeriformes, and family Thraupidae. The genus Paroaria is characterized as monophyletic, indicating that all species within the genus share a common ancestor. Understanding the osteological and anatomical particularities of this species may contribute to future studies involving its biological history, the morphological adaptations that supported its expansion, its ecological niche, as well as assist in veterinary medical procedures for the rescue and rehabilitation of its populations. Six anatomical specimens of adult individuals (three males and three females) of Paroaria dominicana (Linnaeus, 1758) were provided by the Wildlife Screening Center (CETAS), located in the Mata do Amém restinga forest in the city of Cabedelo, Paraíba, Brazil. The skulls were dissected to expose their bony structures, using a stereomicroscope for detailed observation. The bones corresponding to the neurocranium and viscerocranium of the species were described to contribute to its morphological and phylogenetic data. The skulls of Paroaria dominicana (Linnaeus, 1758) presented light and fragile bones, with anatomical particularities associated with their diet. The neurocranium is mainly composed of the frontal, parietal, and occipital bones, with notable features including the cerebellar prominence and multiple foramina at the cranial base. The splanchnocranium, in turn, exhibits large orbits, a well-developed quadrate bone that articulates the beak and mandible, a slender palatine region, and a robust beak with elliptical nostrils. In summary, this study provides a significant contribution to the understanding of the cranial morphology of Paroaria dominicana (Linnaeus, 1758), emphasizing its complex structure and anatomical adaptations.